Studi Literature: Semantik dalam Karya Sastra dan Jenisnya - Zulaikah; Oktaviana, Ajeng; Rahmawati, Anisa; Wijayanti, Dian (Kajian Bahasa dan Sastra (KABASTRA), 2025)
Semantics, as a branch of linguistics that studies meaning in language, plays an important role in literary works by providing depth and richness to texts. Through meaning analysis, writers can communicate complex ideas and deep emotions, creating a richer experience for readers. This research is qualitative research with a literature study method. In literary works, the use of semantics is not only limited to the literal meaning of words, but also involves language games, symbolism, and ambiguity that allow readers to interpret the text from various points of view. By utilizing a variety of semantic techniques, writers can explore universalist themes, evoke feelings, and build relationships between characters and readers, thus making semantics an important tool in the art of storytelling.